Symmetry and multiplicity of solutions in a two-dimensional Landau-de Gennes model for liquid crystals - Ignat, R; Nguyen, L; Slastikov, V; Zarnescu, A (Springer Nature, 2020)
We consider a variational two-dimensional Landau–de Gennes model in the theory of nematic liquid crystals in a disk of radius R. We prove that under a symmetric boundary condition carrying a topological defect of degree 𝑘2 for some given even non-zero integer k, there are exactly two minimizers for all large enough R. We show that the minimizers do not inherit the full symmetry structure of the energy functional and the boundary data. We further show that there are at least five symmetric critical points.